Influence of Mixing Time on the Hardness and Structure of Local Clay-Based Crucibles - Rusiyanto; Rifky Ismail; Athanasius Priharyoto Bayuseno; Daffa Agya Mahardika; Deni Fajar Fitriyana; Wirawan Sumbodo; Aldias Bahatmaka (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Although clay crucibles are frequently utilized in regional industries, their inadequate mechanical strength often causes durability issues. This study investigates the influence of mixing duration on the Vickers hardness and macrostructure of crucibles composed of local clay, kaolin, and molasses. The composition was made up of 47.5% clay, 47.5% kaolin, and 5% molasses as a binder, with 15% water added relative to the total weight. Durations of 15, 30, and 45 minutes were evaluated to determine their impact on material qualities. The findings indicated a positive relationship between mixing duration and hardness. At 15 minutes, the mean hardness was 4.1 HV, which escalated to 8.5 HV at 30 minutes and 12.4 HV at 45 minutes. The increased hardness with extended mixing durations indicates a more homogeneous particle dispersion and enhanced bonding among the raw ingredients. The findings suggest that increasing the mixing time can elevate the quality and longevity of locally manufactured crucibles, rendering them more appropriate for small-scale metallurgical applications.